Is the Male Gender an Independent Risk Factor for Complication in Patients Undergoing Laparoscopic Cholecystectomy for Acute Cholecystitis? - Ambe, Peter C. (Int Surg, 2015)
This paper was designed to investigate the gender dependent risk of complication in patients undergoing laparoscopic cholecystectomy for acute cholecystitis. Laparoscopic cholecystectomy is the standard procedure for benign gallbladder disorders. The role of gender as an independent risk factor for complicated laparoscopic cholecystectomy remains unclear. A retrospective single-center analysis of laparoscopic cholecystectomies performed for acute cholecystitis over a 5-year period in a community hospital was performed. Within the period of examination, 1884 laparoscopic cholecystectomies were performed. The diagnosis was acute cholecystitis in 779 cases (462 female, 317 male). The male group was significantly older (P = 0.001). Surgery lasted significantly longer in the male group (P = 0.008). Conversion was done in 35 cases (4.5%). There was no significant difference in the rate of conversion between both groups. However the rate of conversion was significantly higher in male patients > 65 years (P = 0.006). The length of postoperative hospital stay was significantly longer in the male group (P = 0.007), in the group > 65 years (P = 0.001) and following conversion to open surgery (P = 0.001). The male gender was identified as an independent risk factor for prolonged laparoscopic cholecystectomy on multivariate analysis. The male gender could be an independent risk factor for complicated or challenging surgery in patients undergoing laparoscopic cholecystectomy for acute cholecystitis.